Effects of Jianpi therapy for cancer-related fatigue:a meta-analysis of randomized controlled trials - Dai, Jiaxing; Shui, Huili; Wu, Yuan; Zhang, Huanghui; Li, Yuanyin; Zhang, Shaowang; Yang, Bing; Tang, Dongxin (Frontiers in Oncology, 2025)
PurposeThe Jianpi therapeutic strategy in traditional Chinese medicine aims to enhance the spleen’s digestive function and overall wellness. It has shown promise in improving cancer-related fatigue (CRF). This research systematically evaluates the effectiveness of Jianpi therapy in reducing fatigue in cancer patients through a meta-analytic review.MethodsAn exhaustive search was performed within PubMed, Embase, Web of Science, Cochrane Library, SinoMed, Wanfang Data, China Science and Technology Journal Database, and China National Knowledge Infrastructure (CNKI) for randomized controlled trials concerning the application of Jianpi therapy to address CRF. The search spanned from the commencement of each database’s records to April 1, 2024. The extracted data were subjected to analysis using Stata (Version 15.1), with the selection of either a random-effects or fixed-effects model based on the heterogeneity among studies. Outcome measures were demonstrated with standardized mean differences (SMDs) or mean differences (MDs), and each complemented by a 95% confidence interval (CI). The Cochrane Risk of Bias Assessment Tool 2.0 was utilized to assess the potential biases within the studies.ResultsA comprehensive analysis was performed on 45 eligible studies, all of which were conducted within China and encompassed a total of 3,596 participants. The meta-analysis indicated that Jianpi decoction alone exhibited the most significant improvement in the proportion of CD4 cells (SMD=1.34, 95% CI 0.54 to 2.31, P<0.001) and hemoglobin (MD=7.45, 95% CI 4.18 to 10.72, Z=4.47, P<0.001), while also more significantly reducing Piper Fatigue Scale scores (SMD=-2.05, 95% CI -2.71 to -1.39, P<0.001). The combined therapy, which integrated Jianpi therapy with standard care, demonstrated the greatest advantage in enhancing the proportion of CD3 cells (SMD=1.25, 95% CI 0.46 to 2.04, P<0.001). Furthermore, Jianpi therapy was found to be effective in lowering tumor necrosis factor-alpha levels (MD=-7.79, 95% CI -11.24 to -4.34, P<0.001) and concurrently enhancing interferon-gamma (MD=5.15, 95% CI 3.20 to 7.09, P=0.002), interleukin-2 (MD=8.37, 95% CI 6.14 to 10.59, P<0.001).ConclusionOur research indicates that Jianpi therapy effectively alleviates CRF, reduces inflammation, and strengthens immune function. However, further high-quality, multicenter randomized controlled trials are essential to confirm these findings and strengthen the evidence.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024566739.